Statistical Analysis of the Profile of the Penitentiary Sector of the State of São Paulo (Brazilian Journal of Criminal Execution, 2023)
This article seeks to present and analyze data from the penitentiary sector in the São Paulo state, highlighting the number of workers in the sector by gender, number of people per position, average salary received total and by type of position and gender. As a result, the Penitentiary Administration Secretary of São Paulo has a total of 43,244 employees (6.10% of the total of this state). There are a total of 66 distinct positions in this Secretariat, which were grouped into five categories for analysis. The group with the highest average salary corresponds to Security Agents, followed by the grouping: Others, Escort and Surveillance Agents, and Administrative Officer. In terms of dispersion, the category that presented the greatest salary variability was Others, followed by the categories: Escort and Surveillance Agents, Security Agents and Administrative Officer. There is, in general, a predominance of male employees in this sector. About the remuneration of the employees in the penitentiary sector of São Paulo state by gender, it is verified that the wages received by the employees of the masculine gender, in average, were higher than those received by the employees of the feminine gender; asymmetries occur within each gender.
Keywords: Descriptive Statistics; Penitentiary Sector; Income